2018
DOI: 10.1111/cen.13576
|View full text |Cite
|
Sign up to set email alerts
|

The association between thyroid function and incidence of metabolic syndrome in euthyroid subjects: Tianjin chronic low‐grade systemic inflammation and health cohort study

Abstract: This population-based prospective cohort study suggests that increased serum FT3 level, rather than FT4 and TSH, is an independent predictor for developing MetS in euthyroid subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
2
8
1
Order By: Relevance
“…The mean of BMI of cases was 26.62 ± 2.69 kg/m 2 and in controls it was 24.26 ± 1.56 kg/m 2 . A similar study carried out by Yeqing Gu et al; 15 found that BMI of cases was in range of 25.0-25.3 kg/m 2 and BMI in control group was found to be 23.3 to 25.1 kg/m 2 . Frank M. Bengel et al 16 found that, in cases of hypothyroidism BMI ranges between 25.54 ± 2.18 kg/m2.…”
Section: Discussionsupporting
confidence: 56%
“…The mean of BMI of cases was 26.62 ± 2.69 kg/m 2 and in controls it was 24.26 ± 1.56 kg/m 2 . A similar study carried out by Yeqing Gu et al; 15 found that BMI of cases was in range of 25.0-25.3 kg/m 2 and BMI in control group was found to be 23.3 to 25.1 kg/m 2 . Frank M. Bengel et al 16 found that, in cases of hypothyroidism BMI ranges between 25.54 ± 2.18 kg/m2.…”
Section: Discussionsupporting
confidence: 56%
“…Serum levels of thyroid hormones (THs) have been associated with MetS components since they target the same metabolic pathways ( 5 , 7 ). THs are of major importance for metabolism and energy balance.…”
mentioning
confidence: 99%
“…Thyroid hormones (TH) are essential for cellular energy homeostasis and regulation. These actions are mediated both through the central nervous system and the direct interaction of TH with peripheral target organs [4]. Abnormal levels of THs alter metabolism and these alterations cause a MetS-like picture [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…These actions are mediated both through the central nervous system and the direct interaction of TH with peripheral target organs [4]. Abnormal levels of THs alter metabolism and these alterations cause a MetS-like picture [1,4]. Studies suggest an association between a high thyroid stimulating hormone (TSH) and (individual components of) the MetS [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%